STUDENT AS RESEARCHER: ASSESSMENT ANALYSIS ON INTERCULTURAL LANGUAGE EDUCATION COURSE - Wahyudi, Ribut (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
Context awareness in tertiary education is a crucial aspect. This awareness should be perceived by university students to maximize their academic potentials. In so doing, this mini research employs context analysis about: text, the purpose of text, the setting of text, the audience of text, the relationship between reader and writer, the expectations and conventions and the requirements of texts, shared values, background knowledge and understanding of text, intertextuality, the tone of text, assessment criteria followed by intercommunication of discourse community as proposed by Johns (1997). The context analysis on the disciplinary assignment through the active role of students as researcher is necessary. This would sensitize students what to do and what not to do in the learning activities. Furthermore, being well-informed on ethnographic writing, the study of academic practices in the university, is salient. This can be done, one of them, through the interview with the lecturer of a specific course as well as to some extent negotiate the academic practices. This positions the students as an active agent in learning.Keywords: Student as Researcher, Context Analysis, Ethnographic Writing, Genre